The Effect of CO2 Emissions, Energy Consumption, Coal Consumption on Gross Domestic Product per Capita in Indonesia - Wahyu Aji Wijaya (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2021)
Energy consumption in driving the industrialization of the economy in its development must be accompanied by regulatory policies that support so that this energy can be used efficiently. This study aims to determine the effect of CO2 emissions, energy consumption, and coal use on per capita economic growth in Indonesia. Secondary data used are time series sourced from the World Bank, the Central Bureau of Statistics, and related agencies during the period 1985 to 2019. The analytical tool used in this study is multiple linear regression based on Ordinary Least Square (OLS) along with statistical tests and Classical Assumption Test. The estimation results conducted show that the CO2 emission variable has a significant effect and has a positive relationship to Gross Domestic Product (GDP) per capita in Indonesia and the variables of coal consumption and energy consumption have a negative correlation to GDP per capita and seen from the probability value of the variable coal consumption statistically does not have a significant effect on GDP per capita in Indonesia.